Exercise training and vascular cell phenotype in a swine model of familial hypercholesterolaemia: conduit arteries and veins. Issue 2 (2nd January 2014) - Simmons, Grant H.; Padilla, Jaume; Jenkins, Nathan T.; Laughlin, M. Harold
<x xml:space="preserve">Abstract</x> New Findings What is the central question of this study? Does endurance exercise training cause anti‐atherogenic effects on the endothelium in a swine model of familial hypercholesterolaemia (FH), and how are these effects distributed across veins, arteries and multiple vascular territories within each system? What is the main finding and its importance? Coronary artery endothelium‐dependent vasomotor function was depressed in sedentary FH pigs compared with sedentary control animals, and exercise training did not change vasomotor function within FH. In systemic conduit arteries and veins, few effects of FH on endothelial cell protein expression were noted, including both pro‐ and anti‐atherogenic changes. These findings suggest that exercise training does not produce a consistently improved endothelial cell phenotype in either coronary or systemic conduit vessels in this swine model of FH. Exercise training has emerged as an intervention for the primary and secondary prevention of coronary artery disease, but the mechanisms through which training reduces relative risk are not completely understood. The goal of this study was to investigate the impact of endurance exercise training on vasomotor function and vascular cell phenotype in coronary arteries and systemic conduit arteries and veins against a background of advanced atherosclerosis. We tested the hypothesis that exercise training restores endothelial vasomotor function and produces an anti‐atherogenic endothelial and smooth muscle cell phenotype in familial hypercholesterolaemic (FH) swine. The study included 30 FH (15 exercised and 15 sedentary) and 13 non‐FH control male castrated swine. The exercise‐training intervention consisted of treadmill running 5 days per week for 16–20 weeks. Tissues sampled at sacrifice included vascular rings from the coronary circulation for vasomotor function experiments (dose‐dependent bradykinin‐induced vasorelaxation) and endothelial cells (ECs) from isolated segments of the thoracic aorta, the carotid, brachial, femoral and renal arteries, as well as each corresponding regionally associated vein, and from the abdominal vena cava, the right coronary and internal mammary arteries. Smooth muscle cells were sampled from the right coronary artery only. Vascular cell phenotype was assessed by immunoblotting for a host of both pro‐ and anti‐atherogenic markers [e.g. endothelial nitric oxide synthase, p67phox, superoxide dismutase 1 (SOD1)]. Coronary artery endothelium‐dependent vasomotor function was depressed in sedentary FH pigs compared with sedentary control pigs, and exercise training did not change vasomotor function within FH. In contrast, only scattered effects of FH on EC phenotype were noted across the vasculature, which included both pro‐ and anti‐atherogenic changes in EC protein expression (e.g. increased endothelial nitric oxide synthase in carotid artery ECs, decreased p67phox in brachial artery ECs, but decreased expression of the antioxidant protein SOD1 in thoracic vena cava; all P < 0.05). In thoracic vena cava ECs, this deficit was corrected by exercise training, while no other effects of exercise were observed in conduit vessel EC phenotype. Thus, while exercise training abrogated the adverse effect of hypercholesterolaemia on thoracic vena cava SOD1 expression, it appears that exercise training does not produce a consistently improved EC phenotype in either coronary or systemic conduit vessels in this FH swine model.